Determinants of bank performance in a developing economy: does bank origins matters? - Sufian, Fadzlan; Mohamad Noor, Mohamad Akbar Noor (Sage, 2012)
The article seeks to examine the internal and external factors that influenced the performance of banks operating in the Indian banking sector during the period 2000–08. The empirical findings from this study suggest that credit risk, network embeddedness, operating expenses, liquidity and size have statistically significant impact on the profitability of Indian banks. However, the impact is not uniform across banks of different nations of origin. During the period under study, the empirical findings do not lend support for the ‘limited form’ of global advantage hypothesis. Likewise, the liability of unfamiliarness hypothesis is also rejected, since we do not find significant advantage accruing to foreign banks from other Asian countries.